Ease of Activities of Daily Living with Conventional and Multigrip Myoelectric Hands. Issue 2 (April 2015) - Pröbsting, Eva; Kannenberg, Andreas; Conyers, Daniel W.; Cutti, Andrea Giovanni; Miguelez, John M.; Ryan, Tiffany A.; Shonhowd, Trond Peter
Abstract : ABSTRACT: Introduction: The human hand is greatly complex and makes it possible to manipulate and hold objects using many different grips, whereas the function of traditional myoelectric prosthetic hands is dramatically limited, offering only the tripod grip. Therefore, amputees use the prosthesis actively for only about 50% of activities of daily living (ADLs). The purpose of this study was to investigate whether the Michelangelo hand (Otto Bock HealthCare GmbH, Duderstadt, Germany) offering more grip modes as well as a flexible wrist improves function and reduces perceived difficulty of performing ADLs in comparison to conventional myoelectric hands. Materials and Methods: A questionnaire that combined the validated Orthotics and Prosthetics User Survey–Upper Extremity Functional Status (OPUS-UEFS) and the Prosthetic Upper Extremity Functional Index (PUFI) was used to assess perceived difficulty and usefulness of the prosthesis in performing 23 ADLs. Patients completed this questionnaire at baseline for their existing prosthetic hand and after a minimum of 4 weeks of use of the Michelangelo hand. Results: Sixteen male transradial amputees with an average age of 41 ± 14 years were enrolled. The mean period since amputation was 11.8 ± 16.1 years, and the mean duration of Michelangelo use was 12.4 ± 7.3 weeks. The Michelangelo hand significantly improved the ease of performing the 23 ADLs in the OPUS-UEFS from 27.0 ± 9.7 to 36.4 ± 12.7 ( p = 0.03). The mean total score for bimanual activities improved highly significantly ( p = 0.01) with 26.2 ± 8.1 for Michelangelo as compared with 20.0 ± 7.1 with the previous hand. Using the Michelangelo hand patients performed significantly more ADLs with "both hands together with the prosthetic hand used actively to grasp" as compared with the conventional myoelectric hands (means 9.3 ± 4.6 vs. 7.1 ± 4.1 ADLs; p = 0.04). In addition, the Michelangelo hand was rated as very useful for significantly more ADLs (9.1 ± 4.3 vs. 6.4 ± 4.1 ADLs; p = 0.01). Conclusions: These results suggest that the Michelangelo hand offering more grip types and functional hand positions as well as a flexible wrist may be used more actively and for more ADLs. These effects seem to be promoted by a reduced perceived difficulty to perform many ADLs as Michelangelo shortens the functional gap between prosthetic and sound human hands.